Role of Homework in Learning Achievement: Teachers' Perspectives - Devkota, Krishna Prasad (Journal of Educational Research and Innovation, 2024)
Homework means types of work which is planned and approved by the teacher within certain time of period. Homework has been used for enhance quality of education by connect students to outline of any subject. Many Teachers and parents have been believed that homework can play the important role for improve learning in other hand different scholars and academician has been rise their voice against homework and anti-homework movement also raised in latest time. Different debatable and controversial issues have been raising regarding homework. The study is to find and explore the role of homework for enhancing students learning. Through the in-depth interviews and observation, the study examines teachers' perspectives, experiences, and understanding toward homework. This study has been emphasized to find the role of homework for enhancing students' learning from teachers' perspectives in basic-level education in the Narayan Municipality of the Dailekh district. Especially private schools have been blamed for homework issues. Many students were victims of overloaded homework. In this article I have been trying to explore the role of homework by aligning with students learning achievements through teachers' perspectives. The positive and negative roles of homework and ways of using homework as an effective tool are also described. For preparing this article, I have used the qualitative research approach. Five teachers were selected from two private schools in the Dailekh district through the purposive sampling